Maturation of Pluripotent Stem Cell-Derived Cardiomyocytes Enables Modeling of Human Hypertrophic Cardiomyopathy - Knight, Walter E.; Cao, Yingqiong; Lin, Ying-Hsi; Chi, Congwu; Bai, Betty; Sparagna, Genevieve C.; Zhao, Yuanbiao; Du, Yanmei; Londono, Pilar; Reisz, Julie A.; Brown, Benjamin C.; Taylor, Matthew R.G.; et al. (Stem cell reports, 2021)
Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are a powerful platform for biomedical research. However, they are immature, which is a barrier to modeling adult-onset cardiovascular disease. Here, we sought to develop a simple method that could drive cultured hiPSC-CMs toward maturity across a number of phenotypes, with the aim of utilizing mature hiPSC-CMs to model human cardiovascular disease. hiPSC-CMs were cultured in fatty acid-based medium and plated on micropatterned surfaces. These cells display many characteristics of adult human cardiomyocytes, including elongated cell morphology, sarcomeric maturity, and increased myofibril contractile force. In addition, mature hiPSC-CMs develop pathological hypertrophy, with associated myofibril relaxation defects, in response to either a pro-hypertrophic agent or genetic mutations. The more mature hiPSC-CMs produced by these methods could serve as a useful in vitro platform for characterizing cardiovascular disease. [Display omitted] •Standard (glucose) cultured hiPSC-CMs demonstrate a blunted hypertrophic response•A maturation method induces hiPSC-CM maturation and suppresses HIF1A expression•Mature hiPSC-CMs demonstrate improved sarcomeric morphology and contractility•Mature hiPSC-CMs respond to agonist- or mutation-induced hypertrophy In this article, Song and colleagues show that a combination of fatty acid medium and micropatterned surfaces induces maturation in human induced pluripotent stem cell-derived cardiomyocytes. Matured cells display improved sarcomere morphology, metabolic maturation, and contractility. These cells also show increased sensitivity to hypertrophic stimuli, including hypertrophic agonist and genetic mutations, representing an ideal system to model cardiovascular disease.